Effects of an Explosive Polar Cyclone Crossing the Antarctic Marginal Ice Zone. Issue 11 (12th June 2019) - Vichi, Marcello; Eayrs, Clare; Alberello, Alberto; Bekker, Anriëtte; Bennetts, Luke; Holland, David; de Jong, Ehlke; Joubert, Warren; MacHutchon, Keith; Messori, Gabriele; Mojica, Jhon F.; Onorato, Miguel; et al.
Abstract: Antarctic sea ice shows a large degree of regional variability, which is partly driven by severe weather events. Here we bring a new perspective on synoptic sea ice changes by presenting the first in situ observations of an explosive extratropical cyclone crossing the winter Antarctic marginal ice zone (MIZ) in the South Atlantic. This is complemented by the analysis of subsequent cyclones and highlights the rapid variations that ice‐landing cyclones cause on sea ice: Midlatitude warm oceanic air is advected onto the ice, and storm waves generated close to the ice edge contribute to the maintenance of an unconsolidated surface through which waves propagate far into the ice. MIZ features may thus extend further poleward in the Southern Ocean than currently estimated. A concentration‐based MIZ definition is inadequate, since it fails to describe a sea ice configuration which is deeply rearranged by synoptic weather. Plain Language Summary: The extent of Antarctic sea ice is characterized by large regional variations that are in stark contrast with the alarming decreasing trends found in the Arctic. This is partly due to the presence of severe weather events, like extratropical cyclones travelling through the Southern Ocean and reaching the marginal ice zone (MIZ). The MIZ is a region where the ocean, atmosphere, and sea ice processes are closely interlinked. We provide direct evidence of how winter polar cyclones rearrange the MIZ and how their effects extend into the ice‐covered region as far as the Antarctic continent. We present the first observations of large ice drift, ice concentration, and temperature changes as an explosively deepening cyclone crosses the MIZ. This case study is complemented by analysis of subsequent but more frequent storms that confirms how storminess in the Southern Ocean maintains a sea ice surface that is less compact, more mobile, and more extended than previously anticipated. Our results urge the scientific community to revise the current definition of the MIZ and improve its representation in models to better include the role of polar cyclones in detecting Antarctic sea ice trends. Key Points: We present the first in situ measurements of an explosive polarcyclone crossing the Antarctic marginal ice zone Warm air advection and wave propagation contribute to the maintenance of an unconsolidated sea ice surface far away from the ice edge Polar cyclones reshape the ice‐covered ocean, thus extending the marginal ice zone beyond current definitions